Single procedure revision cranioplasty with intra-operative autoclave following titanium plate exposure. (3rd May 2020) - Moneim, Joseph; Wenlock, Rhys D.; Wells, Adam J.; Price, Richard D.; Timofeev, Ivan; Helmy, Adel; Hutchinson, Peter J.
Abstract: Background: Patients with titanium cranioplasties can develop skin defects and plate exposure requiring revision surgery to prevent infection. The management of these patients has historically been staged surgery to remove the exposed plate followed by re-implantation of a sterile plate at a later date. Objectives: We describe an alternative where the exposed plate is removed, sterilised by autoclaving and re-implanted, in one operation. Methods: Patients with exposed titanium cranioplasties who underwent single-stage revisions were identified over a 30-month period. All patients received antibiotics post-procedure and were followed up. Results: Between June 2015 and December 2017 four patients had five single-stage revision cranioplasties with intraoperative autoclave sterilisation (SSRC). The mean time from initial procedure to revision was 5.6years. The mean time from plate exposure to surgery was 7 days. Plate exposure recurred in 60% (3/5) of cases post-SSRC. Two of these had the plate removed. The other had a second SSRC. On average recurrent plate exposure developed 17 months after SSRC. The 2 cases who had the plate removed remained complication-free to last follow up at 25 and 52 months after SSRC. Conclusions: Single procedure revision cranioplasty with intra-operative autoclave following titanium plate exposure may be considered as an option in patients with plate exposure who do not have other evidence on infection but we found recurrent plate exposure occurred in 50%.